Brother Sun, Sister Moon: The Lunar Cycle, Sunspots and the Frequency of Births - Thomas K. Bauer; Stefan Bender; Jörg Heining; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Based on multivariate linear regression models, we analyze the effect of the lunar cycle and the number of sunspots occurring on a particular day on the number of births using social security data and controlling for a number of other potential confounders. The daily number of births between 1920 and 1989 have been calculated from the full sample of individuals who have been registered at least once in the German social security system. While the lunar cycle does not affect the number of births, the number of sunspots has a positive, albeit small effect on the number of births which is decreasing over time. The empirical results may be explained by medical technological progress making natural influences on births less important over time. This interpretation is supported by the results on the intertemporal influence of weekends and holidays on the frequency of daily births.
Keywords: I12; J13; 330; daily frequency of births; lunar cycle; sunspots